2020
DOI: 10.3389/fmicb.2020.00352
|View full text |Cite
|
Sign up to set email alerts
|

Metadata Analysis of mcr-1-Bearing Plasmids Inspired by the Sequencing Evidence for Horizontal Transfer of Antibiotic Resistance Genes Between Polluted River and Wild Birds

Abstract: We sequenced the whole genomes of three mcr-1-positive multidrug-resistant E. coli strains, which were previously isolated from the environment of egret habitat (polluted river) and egret feces. The results exhibit high correlation between antibiotic-resistant phenotype and genotype among the three strains. Most of the mobilized antibiotic resistance genes (ARGs) are distributed on plasmids in the forms of transposons or integrons. Multidrug-resistant (MDR) regions of high homology are detected on plasmids of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…Escherichia coli isolates carrying mcr-1 on transferable IncHI2 plasmids were detected in on-site preflooder downstream the discharge point of mWWTP. Possible entry sources could be run-offs from the fields fertilized with contaminated manure (Guenther et al, 2017) and feces of wild animals (birds) (Lin et al, 2020). Previously, (Zurfluh et al, 2016) and (Falgenhauer et al, 2019) detected mcr-1 harboring E. coli in surface water and rivers in Switzerland and Germany, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli isolates carrying mcr-1 on transferable IncHI2 plasmids were detected in on-site preflooder downstream the discharge point of mWWTP. Possible entry sources could be run-offs from the fields fertilized with contaminated manure (Guenther et al, 2017) and feces of wild animals (birds) (Lin et al, 2020). Previously, (Zurfluh et al, 2016) and (Falgenhauer et al, 2019) detected mcr-1 harboring E. coli in surface water and rivers in Switzerland and Germany, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of mcr on plasmids, many studies have been conducted on mcr -carrying plasmids of COR bacteria isolated from various sources. 7 , 8 , 18 , 19 Outcomes of a metadata analysis revealed that the mcr -carrying plasmids are diverse. 19 Among these mcr -carrying plasmids, IncI2, IncX4, and IncHI2 plasmids are found most frequently, even in livestock isolates.…”
Section: Discussionmentioning
confidence: 99%
“… 7 , 8 , 18 , 19 Outcomes of a metadata analysis revealed that the mcr -carrying plasmids are diverse. 19 Among these mcr -carrying plasmids, IncI2, IncX4, and IncHI2 plasmids are found most frequently, even in livestock isolates. The outcomes of the present study regarding mcr-1 -harboring plasmid IncHI2 of the livestock COR isolate are consistent with those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…The role of migratory birds in facilitating the transfer of antibioticresistant bacteria and resistance genes has been gradually recognized (Guenther et al, 2012;Atterby et al, 2016;Ramey et al, 2018;Marcelino et al, 2019). The potential of intercontinental transportation of antibiotic-resistant bacteria and resistance genes via avian migration was also proposed (Liakopoulos et al, 2016;Mohsin et al, 2016;Lin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…However, N150,000 migratory birds use this lake as breeding or stopover ground annually (Zheng et al, 2018). In our previous work, we reported the transportation of bacterial antibiotic resistance from a polluted urban river (Jin River, Chengdu, China) to surrounding environment (Wangjianglou Park) mediated by the wild birds (the egrets) (Wu et al, 2018;Lin et al, 2020). In the similar manner, the migratory birds may transport antibiotic-resistant bacteria or resistance genes from other places along the migration route to the environment around Qinghai Lake.…”
Section: Introductionmentioning
confidence: 99%